2012
DOI: 10.1016/j.talanta.2012.07.091
|View full text |Cite
|
Sign up to set email alerts
|

Multi-class determination of personal care products and pharmaceuticals in environmental and wastewater samples by ultra-high performance liquid-chromatography-tandem mass spectrometry

Abstract: In this work, a multi-class method for the simultaneous determination of 17 emerging contaminants, including pharmaceuticals and personal care products, has been developed.Target analytes were two anti-inflammatories, a lipid regulator agent, two angiotensin II antagonists, two antiepileptic drugs and a diuretic. Among personal care products, four preservatives and five UV filters were included. The method is based on solid-phase extraction (SPE) using Oasis HLB cartridges followed by ultra-high performance li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 31 publications
0
39
0
12
Order By: Relevance
“…In the work reported here, we studied the kinetics and equilibrium of adsorption onto commercial granular activated carbon of three emergent contaminants: methylparaben (Mp), carbamazepine (Cbz), and sildenafil citrate (Sil); those selected as being representative of such pollutants in wastes within the environment [1] [2]. The objective of this investigation was to provide new information in order to gain a better understanding of the parameters and mechanisms involved in the processes of adsorption and to develop a technique for the removal of pharmaceuticals and personal-care products (PPCPs) from urban wastewaters that would be applicable to full scale.…”
Section: Introductionmentioning
confidence: 99%
“…In the work reported here, we studied the kinetics and equilibrium of adsorption onto commercial granular activated carbon of three emergent contaminants: methylparaben (Mp), carbamazepine (Cbz), and sildenafil citrate (Sil); those selected as being representative of such pollutants in wastes within the environment [1] [2]. The objective of this investigation was to provide new information in order to gain a better understanding of the parameters and mechanisms involved in the processes of adsorption and to develop a technique for the removal of pharmaceuticals and personal-care products (PPCPs) from urban wastewaters that would be applicable to full scale.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to traditional SPE, different SPE sorbents have been employed depending on the nature of the target compounds, due to the different polarity when comparing triclosan, parabens or isothiazolinones. Thus, non-polar C18 [79,105,122] is used in few cases for triclosan, while PS-DVB modified sorbents [27,37,50,107] or PVP-DVB-based sorbents [28,33,43,67,110,111,115,128] that promote polar and non-polar interactions are preferred when more polar compounds like parabens, isothiazolinones or other PCPs are determined, trying to cover a wide range of retention capacity. It should be mentioned the paper published by Gorga et al [131] who proposed on-line SPE for the determination of different PCPs including some preservatives.…”
Section: Preservativesmentioning
confidence: 99%
“…PPCPs enter into the environment through individual human activity and as residues from agriculture, manufacturing, veterinary use, as well as community and hospital use [1]. Numerous studies have reported PPCP residues in waste water treatment plant (WWTP) influents and effluents, as well as surface waters, with concentrations generally ranging between 0.001 and 1 g/L [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%